Pengaruh variasi plating masa kini terhadap dimensi meja makan restoran - Setiamurti Rahardjo; Victorina Geraldine; Ahmad Muzzayin Dina Wari (Institut Seni Indonesia Yogyakarta, 2021)
Along with the times, the human lifestyle also continues to develop, this also affects the facilities of public space one of which is a restaurant. In the present era, the restaurant is used not only for places to eat and drink but also as a gathering place, relax, or as other self-image accommodation. This makes the restaurant also develops following the development of human lifestyle trends today, ranging from building design, room, furniture, tableware, to the way of serving food and drinking or plating variations in the restaurant. The development of plating variation is also adjusted from the style, shape, and dimensions of the tableware used by adjusting the type, theme and menu of the current trend. Today, one of Indonesia's many cities has its culinary tourism area is Bandung. Therefore, the authors conducted research on several popular restaurants in Bandung such as 180 Coffee and Music, Al Jazeerah Signature, Miss Bee Providore, and Gormeteria regarding variations in present plating to individual plating variations, plating variations when there were sharing items, variations in plating when there were other items from the current lifestyle section such as cellphones, wallets, and so on, so that they can find out the effect of variations in current plating on the dimensions of the restaurant dining table.